STUDI KOMPARASI UPAYA PREVENTIF PERILAKU LGBT PADA KELUARGA PERSPEKTIF FIQIH SUNNAH DAN HUKUM NEGARA INDONESIA - Lensa, Hendri Waluyo; Siti Nazla Raihana (Al-Usariyah: Jurnal Hukum Keluarga Islam, 2023)
Deviant behavior in sexual orientation, known as lesbian, gay, bisexual, and transgender, which is more commonly referred to as LGBT, has had a negative impact on social security in society. This is the result of the globalization of LGBT, and the lack of public knowledge about LGBT, religious, and state norms. This study aims to polarize religious laws and then compare them with state norms and laws on preventive patterns of LGBT behavior. The analysis used in this study is a descriptive-analytical method, namely carefully describing preventive patterns of LGBT behavior which are embodied in one source of Islamic law, namely sunnah and its explanations and state law which is embodied in the Criminal Code (KUHP). Based on the results of this study, it was found that there were differences in preventive patterns of LGBT behavior in the perspective of fiqh sunnah and the perspective of Indonesian state law. Preventive patterns of LGBT behavior from the perspective of fiqh sunnah are more assertive in prohibiting the daily behavior of family members which will stimulate a person's psyche to deviate sexual behavior. As for Indonesian state law, preventive measures are looser and less comprehensive. This study recommends that the Criminal Code law be revised again using the applicable mechanism by taking into account the Islamic religious norms embodied in fiqh sunnah.